The Effect of Rates and Service Quality Towards The Customer Satisfaction of PT Pelabuhan Indonesia III (Persero) Banjarmasin Branch - Mawan Budiyanto; RR Yulianti Prihatiningrum (Journal of Social Science, 2021)
This study aims to analyze the effect of rates (X1), interactions quality (X2), physical environment quality (X3), and outcomes quality (X4) as partially independent variables on the customer satisfaction (Y) as the dependent variable on users of ship guidance services at PT Pelabuhan Indonesia III (Persero) Banjarmasin Branch. Data were collected by distributing questionnaires to 115 respondents. The samples were determined based on the total sampling technique. There were 115 respondents chosen as the samples. The research site was at PT. Pelabuhan Indonesia III (Persero) Banjarmasin Branch. The unit of analysis was all customers at PT. Pelabuhan Indonesia III (Persero) Banjarmasin Branch. Measurement of variables was conducted using the Likert scale technique with a scale of weights from 1 to 5. These were meant to analyze the effect of variable rates (X1), quality of interactions (X2), quality of physical environment (X3), and quality of results (X4) on customer satisfaction (Y) using techniques multiple linear regression statistics. The results showed that the variable rates (X1), interactions quality (X2), physical environment quality (X3), and outcomes quality (X4) has a positive and significant effect on customer satisfaction partially on PT. Indonesian Port III, Banjarmasin Branch. and outcomes quality (X4) partially had a positive and significant effect on customer satisfaction at PT. Indonesian Port III, Banjarmasin Branch. and outcomes quality (X4) partially had a positive and significant effect on customer satisfaction at PT. Indonesian Port III, Banjarmasin Branch.